2017
DOI: 10.1177/0308518x17725074
|View full text |Cite
|
Sign up to set email alerts
|

Governmentalizing Gramsci: Topologies of power and passive revolution in Cambodia’s garment production network

Abstract: This article takes a fresh look at the multiple power relations between state, capital and labor in global production networks. Moving beyond debates about public vs. private governance, it brings together Antonio Gramsci's concepts of hegemony and the integral state with Michel Foucault's concepts of governmentality and the ''dipositive'' in order to analyze the power topologies that permeate global production networks. Using the Cambodian garment production network as example, we scrutinize the discourse of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…On the other hand, research has explored how GPNs are articulated with the state and how state policy and trade regulation seeks to establish new geographic frontiers for capital accumulation (Glassman 2011;Smith 2015a; see also Horner 2017). Together, this work has its parallels with Levy's (2008, 944) "understanding of GPNs as integrated economic political systems" (see also Arnold and Hess 2017).…”
Section: Economic Geographymentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, research has explored how GPNs are articulated with the state and how state policy and trade regulation seeks to establish new geographic frontiers for capital accumulation (Glassman 2011;Smith 2015a; see also Horner 2017). Together, this work has its parallels with Levy's (2008, 944) "understanding of GPNs as integrated economic political systems" (see also Arnold and Hess 2017).…”
Section: Economic Geographymentioning
confidence: 99%
“…10 The result has been an increased concentration of power among a smaller group of retailers in many EU countries and cost pressures down the value chain impacting on suppliers. As research on the sector has shown, these interfirm relations are characterized by significant power asymmetries between lead firm and suppliers (Gereffi 1994;Smith 2003;Werner 2016), which are embroiled in wider networks of power struggles between social actors (Arnold and Hess 2017).…”
Section: Labor Regimes and Gpnsmentioning
confidence: 99%
“…Dawkins & Lewis, 2003) and political CSR frameworks (e.g. Scherer & Palazzo, 2011), the neo-Gramscian approach provides a more historical and dynamic understanding of the changing power relations in the process of hegemony-building (see Levy & Spicer, 2013; Morton, 2010), a subtler understanding of the role of civil society in organizational interactions with state and business (see Spicer & Böhm, 2007; MacKay & Munro, 2012) and a more sophisticated understanding of processes of challenging and accommodating (see Arnold & Hess, 2017). With increasingly pluralistic yet contested roles of government agencies, corporations and civil society actors in re-organizing China’s rare-earth industry, the neo-Gramscian perspective highlights the need to centre the analysis on multiple actors, investigating the diversity of micro-level organizational processes in the hegemony-building processes of China’s passive revolution.…”
Section: Resultsmentioning
confidence: 99%
“…The OS field lacks somewhat behind other social science fields where there are a number of empirical studies that discuss the role of the state in relation to the political-economic formations of non-Western contexts. For example, Arnold and Hess (2017) governmentalize Gramsci in Cambodia's garment industry to discuss the interaction between labour struggles and state responses; Abrahamsen (1997) provides a holistic analysis of democratization in Africa; and Morton (2010) situates passive revolutions in diverse varieties of non-western contexts, covering Latin American, East Europe, and East Asia. There is hence a need in OS to go beyond Western-centric, neo-Gramscian environmental governance research to include non-Western contexts, specifically understanding better the organization of hegemonic systems dominated by the state.…”
Section: The Neo-gramscian Approach In and Beyond Osmentioning
confidence: 99%
“…Tran et al, 2017; Smith et al, 2018; see also Berliner et al, 2015). Arnold and Hess (2017) offer a useful assessment of one such initiative, an ILO-led labor compliance program for export zones in Cambodia. They argue that the program secures legitimacy for a state that relies upon both coercive power to quell protest and consent-building through civil society dialogue.…”
Section: Where and Why State Roles Combine: Theorizing The State-mentioning
confidence: 99%